2013
DOI: 10.1007/s00277-013-1964-1
|View full text |Cite
|
Sign up to set email alerts
|

The KIT D816V expressed allele burden for diagnosis and disease monitoring of systemic mastocytosis

Abstract: The activating KIT D816V mutation plays a central role in the pathogenesis, diagnosis, and targeted treatment of systemic mastocytosis (SM). For improved and reliable identification of KIT D816V, we have developed an allele-specific quantitative real-time PCR (RQ-PCR) with an enhanced sensitivity of 0.01-0.1 %, which was superior to denaturing high-performance liquid chromatography (0.5-1 %) or conventional sequencing (10-20 %). Overall, KIT D816 mutations were identified in 146/147 (99 %) of patients (D816V, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 37 publications
1
115
0
Order By: Relevance
“…However, careful analysis of the literature shows discrepant results regarding both the frequency of systemic mastocytosis cases who are KIT D816V + in peripheral blood and the prognostic impact of the KIT D816V allele burden. Thus, while Kristensen et al 9,29 reported positive rates in peripheral blood samples of indolent systemic mastocytosis cases between 96% and 100%, Erben et al 30 only found 46% of indolent systemic mastocytosis patients to be positive in peripheral blood using a different allele-specific quantitative real-time PCR method. In turn, whereas Erben et al 30 suggested that a greater amount of KIT D816V + cells in peripheral blood is associated with a poorer outcome, the Danish group 15 did not find any correlation between the allele burden for the KIT D816V mutation and the clinical manifestations of indolent systemic mastocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, careful analysis of the literature shows discrepant results regarding both the frequency of systemic mastocytosis cases who are KIT D816V + in peripheral blood and the prognostic impact of the KIT D816V allele burden. Thus, while Kristensen et al 9,29 reported positive rates in peripheral blood samples of indolent systemic mastocytosis cases between 96% and 100%, Erben et al 30 only found 46% of indolent systemic mastocytosis patients to be positive in peripheral blood using a different allele-specific quantitative real-time PCR method. In turn, whereas Erben et al 30 suggested that a greater amount of KIT D816V + cells in peripheral blood is associated with a poorer outcome, the Danish group 15 did not find any correlation between the allele burden for the KIT D816V mutation and the clinical manifestations of indolent systemic mastocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while Kristensen et al 9,29 reported positive rates in peripheral blood samples of indolent systemic mastocytosis cases between 96% and 100%, Erben et al 30 only found 46% of indolent systemic mastocytosis patients to be positive in peripheral blood using a different allele-specific quantitative real-time PCR method. In turn, whereas Erben et al 30 suggested that a greater amount of KIT D816V + cells in peripheral blood is associated with a poorer outcome, the Danish group 15 did not find any correlation between the allele burden for the KIT D816V mutation and the clinical manifestations of indolent systemic mastocytosis. Overall, such apparently discrepant results could be explained by the fact that different approaches were used to assess peripheral blood involvement by the KIT mutation (analysis on gDNA 9,13 vs cDNA 30 ), which therefore might have different sensitivities.…”
Section: Discussionmentioning
confidence: 99%
“…6 Nextgeneration deep amplicon sequencing by 454 FLX amplicon chemistry (Roche, Penzberg, Germany) was performed to investigate 18 genes recurrently mutated in myeloid neoplasms as previously described. 9 …”
Section: Gene Mutation Analysesmentioning
confidence: 99%
“…5 Activating mutations in the receptor tyrosine kinase KIT, usually KIT D816V, are pathogenetically relevant somatic point mutations, detected in >80-90% of patients with SM. 6,7 The multi-lineage expansion by KIT D816V and the KIT D816V allele burden (AB) have an important impact on disease phenotype and prognosis. 6,[8][9][10] Furthermore, the presence and number of molecular aberrations, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation